A New Case of Granulomatosis with Polyangiitis Presented with Tolosa–Hunt Syndrome Manifestations - Maryam Mohebbi; Shahriar Nafissi; Majid Alikhani (Case Reports in Rheumatology)
Background. Tolosa–Hunt syndrome (THS) is a rare disorder involving the orbital and retro-orbital space. The typical symptoms include sensory loss in the trigeminal nerve’s distribution, orbital pain, swelling, headaches, and cranial nerve palsies. Case Presentation. We report a 40-year-old female who initially presented with biparietal headache, unresponsive to medication, which then led to ophthalmoplegia and orbital pain. Serological findings demonstrated positive CANCA-PR3. She was initially treated with 1 g pulse methylprednisolone for three days. Based on the rheumatological evaluation and her positive lung nodule, hematuria, dysmorphic red blood cells, and positive antiproteinase 3 classic antineutrophil cytoplasm antibodies (CANCA-PR3) and also based on the diagnostic criteria for granulomatosis with polyangiitis criteria for Wegner disease, her treatment was continued with prednisolone 1 mg/kg and also rituximab at the first and 14th day of treatment. Conclusion. In our case of THS, we achieved satisfactory improvement in symptoms through the administration of high-dose steroids.